UJI AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN MATOA (Pometia pinnata) PADA MENCIT JANTAN - Moerfiah Moerfiah; Ihat Ismawat; Triastinurmiatiningsih Triastinurmiatiningsih (UIN Sunan Gunung Djati Bandung, 2023)
Matoa empirically has been used by the people of Indonesia as an antidiarrheal drug. The phytochemical test of matoa leaves contains phenolic and flavonoid which are efficacious as astringents and can stop diarrhea. The purpose of this study was to determine the effectiveness of the ethanolic extract of matoa leaves as an antidiarrheal in male mice. Twenty-five male mice were divided into 5 groups with each treatment having 5 replications. The treatment doses of ethanol extract of matoa leaves tested were: dose I (3mg/20 g BW), dose II (6 mg/20g BW), dose III (12mg/20 g BW) and positive control (loperamide 0.02 mg/20 g BW) and negative control (1% CMC suspension). The results obtained in this study that matoa leaves are effective as antidiarrheal, a dose of 12 mg/20g BW is the most effective and equivalent to positive control (loperamide 0.02 mg/20g BW).